Analisis persediaan barang dagang berdasarkan PSAK No. 14 pada Zoya Ponorogo - Kholimaturrohmah , Maulida; Firdausi Mustoffa, Ardyan (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The establishment of Danantara, Indonesia’s sovereign wealth fund (SWF), reflects The increasingly intense business competition demands companies to continuously enhance operational efficiency, including in inventory management. This article aims to analyze the compliance of merchandise inventory recording and valuation at Zoya Ponorogo based on PSAK No. 14. The study employs a descriptive qualitative approach with data collected through structured interviews and documentation. The findings reveal that Zoya Ponorogo has implemented a perpetual inventory recording system combined with the moving average method. This system is operated through the Dealpost application, enabling real-time transaction recording and more accurate calculation of the cost of goods sold (COGS). The analysis shows that approximately 80% of Zoya Ponorogo’s inventory accounting practices align with PSAK No. 14, particularly in terms of purchase cost recording and COGS recognition. However, there are still shortcomings related to net realizable value (NRV) testing and disclosure in financial statements. Therefore, improvements are needed in compliance aspects to ensure the existing system is more comprehensive and adheres fully to accounting standards.